APPLICATION OF «BIGDATA» IN AN ASSESSMENT OF MIGRATORY PROCESSES - U. Musin; I. Nusratullin (Вестник университета)
Today the statistics of migratory processes has a number of shortcomings. Questions of mistakes in the account, a problem of illegal migration, weak methodological base of an assessment of interregional and intraregional migration. In this regard there is a need for development of new methodology according to the analysis of migration for the purpose of increase in relevance and accuracy of an assessment of the mechanical movement of the population. In this research the possibility of application of «big data» in migration statistics is considered, problems which can arise at the same time, and also ways of their overcoming are analyzed.